Masters of illusion : American leadership in the media age - Rosefielde, Steven; Mills, Daniel Quinn (Cambridge ; New York : Cambridge University Press, 2007)
Assesses the forces that will buffet the United States and the global order through 2050.
A world wounded -- Long-term economic realism -- "Smooth comforts false" -- the illusions that confuse us -- Towers of illusion: dysfunctional behaviors -- Mythomaniacs: the sources of our illusions -- Champions of freedom or imperialists: how we're perceived -- We're different now -- The economic roots of American power -- Economic disparities among nations -- Geopolitical aspirations of the nations -- A witch's brew of troubles: the next big wars -- The Middle East -- Strategic independence: an ounce of prevention -- America as mature superpower -- The dangers of overreach -- The transatlantic trap -- The middle course -- How public culture inhibits presidential leadership -- Choosing a great president -- Master of illusions.
Includes bibliographical references (pages 509-523) and index.
Print version record.
eBooks on EBSCOhost
Keywords: USA -- Government; Government information -- United States; Political culture -- United States; National security -- United States; United States -- Politics and government; Information sur l'État -- États-Unis.; Culture politique -- États-Unis.; Sécurité nationale -- États-Unis.; États-Unis -- Politique et gouvernement; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Government information; National security; Political culture; Politics and government; United States; Innere Sicherheit; Politische Führung; Politische Kultur; Electronic books; Electronic books